2011
DOI: 10.1002/jsfa.4561
|View full text |Cite
|
Sign up to set email alerts
|

Wheat‐ and barley‐based diets with or without additives influence broiler chicken performance, nutrient digestibility and intestinal microflora

Abstract: Enzyme supplementation to a wheat- and barley-based diet significantly improved the apparent digestibility of dietary fat. All four additives had a beneficial effect on the intestinal microflora of broilers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 36 publications
2
33
0
6
Order By: Relevance
“…It is speculated that diets effect in birds could in some extent be exerted through their influence on gut microflora responses. Rodriguez et al (2012) reported that digesta count of Escherichia coli and Lactobacilli in the birds fed with wheat-based diets was greater than those received corn-based diets. These bacteria mainly produce acetic and butyric acid, respectively (Guilloteau et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that diets effect in birds could in some extent be exerted through their influence on gut microflora responses. Rodriguez et al (2012) reported that digesta count of Escherichia coli and Lactobacilli in the birds fed with wheat-based diets was greater than those received corn-based diets. These bacteria mainly produce acetic and butyric acid, respectively (Guilloteau et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary enzymes, such as xylanase and β-glucanase, increase intestinal lactic acid bacteria and decrease the population of adverse and pathogenic bacteria such as E. coli. 80 Dietary supplementation with xylanase and β-glucanase can also offer chickens some protection against necrotic enteritis as the enzymes break down the non-starch polysaccharides in the diet and reduce the digesta viscosity. [81][82][83] Dietary inclusion of some plant-derived essential oils has also been used to protect chickens from enteric disease.…”
Section: Interactions Between Gut Microbiome and Dietmentioning
confidence: 99%
“…The mechanisms involved in poor digestibility are not fully understood but it is recognized that viscosity reduces the intestinal passage rate (van der Klis et al, 1993), reduces the diffusion of digestive enzymes and stimulates bacterial proliferation in the small intestine (Choct, 2006;Rodriguez et al, 2012). Moreover, the water-holding capacity brought about by soluble NSP markedly influenced voluntary feed intake.…”
Section: Dietary Treatmentmentioning
confidence: 99%
“…Moreover, the water-holding capacity brought about by soluble NSP markedly influenced voluntary feed intake. The breakdown of these NSPs via enzyme addition contributes to decrease viscosity of the gut contents (Bedford and Classen, 1992), improving feed intake and efficiency of nutrient utilization (Mathlouthi et al, 2002;Choct et al, 2004;Shakouri et al, 2009;Bedford and Partridge, 2010;Rodriguez et al, 2012).…”
Section: Dietary Treatmentmentioning
confidence: 99%